Tactile input and empathy modulate the perception of ambiguous biological motion - Yiltiz, Hörmetjan; Chen, Lihan (Frontiers in Psychology, 2015)
Evidence has shown that task-irrelevant auditory cues can bias perceptual decisions regarding directional information associated with biological motion, as indicated in perceptual tasks using point-light walkers (PLWs) (Brooks et al., 2007). In the current study, we extended the investigation of cross-modal influences to the tactile domain by asking how tactile input resolves perceptual ambiguity in visual apparent motion, and how empathy ability plays a role in this cross-modal interaction. In Experiment 1, we simulated the tactile feedback on the observers’ fingertips when the (upright or inverted) PLWs (comprised of either all red or all green dots) were walking (leftwards or rightwards). The temporal periods between tactile events and critical visual events (the PLW’s feet hitting the ground) were manipulated so that the tap could lead, synchronize, or lag with the visual foot-hitting-ground event. We found that the temporal structures between tactile (feedback) and visual (hitting) events systematically modulate the directional perception for upright PLWs, making either leftwards or rightwards more dominant. However, this temporal modulation effect was absent for inverted PLWs. In Experiment 2, we examined how empathy ability modulates cross-modal capture. Instead of generating tactile feedback on participant’s fingertips, we gave taps on their ankles and presented the PLWs with motion directions of approaching (facing towards observer)/receding (facing away from observer) to resemble normal walking postures. With the same temporal structure, we found that individuals with higher empathic ability were more subject to perceptual bias in the presence of tactile feedback. Taken together, our findings showed that task-irrelevant tactile input can resolve the otherwise ambiguous perception of the directional information of biological motion, whereas cross-modal modulation was mediated by higher level social-cognitive factors, including empathic ability.